An ELISA Method to Compute Endpoint Titers to Epstein-Barr Virus and Cytomegalovirus: Application to Population-Based Studies - Stowe, Raymond P. (2014)
Indirect fluorescence analysis (IFA), the gold standard for determining herpesvirus antibody titers, is labor-intensive and poorly suited for large population-based studies. The enzyme-linked immunosorbent assay (ELISA) is used widely for measuring antiviral antibodies but also suffers drawbacks such as reduced specificity and the qualitative nature of the results due to limited interpretation of the optical density (OD) units. This paper describes a method to titer herpesvirus antibodies using microplates coated with virally-infected cells in which a standard curve, derived from IFA-scored samples, allowed OD units to be converted into titers. A LOOKUP function was created in order to report the data as traditional IFA-based (i.e., 2-fold) titers. The modified ELISA correlated significantly with IFA and was subsequently used to compute endpoint antibody titers to Epstein-Barr virus (EBV)-virus capsid antigen (VCA) and cytomegalovirus (CMV) in blood samples taken from 398 pregnant Hispanic women. Four women were EBV negative (1%), while 58 women were CMV negative (14.6%). EBV VCA antibody titers were significantly higher than CMV antibody titers (p <0.001). This method allows titering of herpesvirus antibodies by ELISA suitable for large population-based studies. In addition, the LOOKUP table enables conversion from OD-derived titers into 2-fold titers for comparison of results with other studies.